Inkjet‐Printed p‐NiO/n‐ZnO Heterojunction Diodes for Photodetection Applications - Sergio González; Giovanni Vescio; Juan Luis Frieiro; Alina Hauser; Flavio Linardi; Julian López‐Vidrier; Marek Oszajca; Sergi Hernández; Albert Cirera; Blas Garrido (Advanced Materials Interfaces, 2023)
Abstract Transparent Conducting Oxides (TCOs) are an enticing family of optoelectronic materials which have been proven to increase efficiency when incorporated into perovskite light emitting diode (PE‐LED) and organic OLED architectures as transport layers. Solution‐processed metal oxide inks have already been demonstrated, although there is still a need for high‐quality inkjet‐printable metal oxide inks with a thermal post‐process below 200 °C. The set of inks in this work are adapted from low‐boiling point colloidal suspensions of metal oxide nanoparticles synthesized via flame spray pyrolysis. High quality, pinhole‐ and wrinkle‐free inkjet‐printed layers are obtained at low temperatures through vacuum oven post process, as proven by scanning electron microscopy. The crystallinity of the layers is confirmed by X‐ray diffraction, showing the expected hexagonal and cubic structures respectively for ZnO and NiO. The thin film layers reach over 70% (ZnO) and 90% (NiO) transparency in the visible spectrum. Their implementation in the inkjet‐printed p–n diode shows excellent I–V rectifying behavior with an ON/OFF ratio of two orders of magnitude at ±3 V and a forward threshold voltage of 2 V. Furthermore, the device exhibits an increase in photocurrent around four orders of magnitude when illuminated under a 1‐sun solar simulator.